Využití alternativních surovin v technologii pískového pórobetonu - Ondříčková, Pavlína (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Práce se zabývá problematikou náhrady křemičitého písku alternativními surovinami ve výrobě pískového pórobetonu. Popisuje technologii výroby a vytváření struktury pórobetonu. Hlavní součástí práce je studium odborných článků zabývajících se alternativními surovinami v autoklávovaných silikátových materiálech. Cílem práce je nalezení nejvhodnějších tuzemských druhotných surovin pro doplnění nebo částečnou náhradu křemičitého písku při výrobě pórobetonu.

The presented work deals with the problems about silica sand replacement for alternative raw materials in the production of autoclaved aerated concrete. The work describes technology of production and creating structures of autoclaved aerated concrete. The main part of the work is the study scientific articles dealing with alternative materials in autoclaved silicate materials. The object of work is to find the most suitable domestic alternative materials for supplement or replacement for silica sand in production of autoclaved aerated concrete.
Utilization of alternative raw materials in sand aerated concrete technology
Keywords: Autoklávovaný pórobeton; křemičitý písek; alternativní suroviny; tobermorit; recyklované sklo.; Autoclaved aerated concrete; silica sand; alternative raw materials; tobermorite; recycled glas.